2018
DOI: 10.1111/joic.12558
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for in‐stent restenosis requiring rotational atherectomy

Abstract: TLR at 12 months is dismal. RA is not effective for ISR requiring RA. In unfavorable settings, DCB angioplasty following RA is the most effective treatment option in patients with ISR requiring debulking strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…The calcified character of ISR in HD patients poses a great challenge in treatment. In a previous series, we found that ROTAfacilitated PCI was a safe and efficient technique for the treatment of ISR but was still related to a high MACE rate (25). Further, in our present data of HD patients, ISR lesions had an even worse outcome than de novo lesions.…”
Section: Discussionsupporting
confidence: 50%
“…The calcified character of ISR in HD patients poses a great challenge in treatment. In a previous series, we found that ROTAfacilitated PCI was a safe and efficient technique for the treatment of ISR but was still related to a high MACE rate (25). Further, in our present data of HD patients, ISR lesions had an even worse outcome than de novo lesions.…”
Section: Discussionsupporting
confidence: 50%
“…21 Rotational atherectomy is also applied to restenotic lesions caused by underexpansion, but long-term outcomes have not been satisfactory. 22 In the present study and although atherectomy was applied in patients with under-expanded stents, the final MLD was similar between those with and without atherectomy. The impact of atherectomy should be studied in the future.…”
Section: Discussionsupporting
confidence: 44%
“…In a retrospective analysis of 200 patients undergoing RA for ISR, 12-month TLR rates were lower for drug-coated balloon angioplasty (27.3%) compared with conventional balloon angioplasty (40.7%) or DES implantation (35.0%), suggesting that for severe ISR requiring a debulking strategy, drug-coated balloon angioplasty following RA might be the most effective treatment option. [42] Other reports have also reported favourable results with drug-coated balloon angioplasty following RA for severe ISR. [43] Nonetheless, stent ablation with RA should be used with extreme caution by highly experienced operators, ideally with on-site surgical backup.…”
Section: Indications and Clinical Outcomesmentioning
confidence: 99%